Peran Minat Beli Dalam Membangkitkan Impulsive Buying - Obing Zaid Sobir; Aprih Santoso (ARBITRASE: Journal of Economics and Accounting, 2022)
The research objective is to determine the effect of price, location and service on Impulsive Buying with Buying Interest as moderator. The total sample is 338 respondents in DKI Jakarta Province, and those who meet the requirements and provide responses. The research method uses a quantitative approach, with a descriptive verification research type. The results of the study are that price has a positive effect on buying interest and its impact on impulse buying. Location has a positive and significant effect on impulse buying. The test results are in line with the hypothesis where there is a positive and significant effect between location on buying interest and its impact on impulse buying. Based on the results of hypothesis testing there is a positive and significant effect. service has a positive effect, based on the test results it can be seen that the b3 coefficient is -0.858 with a significance value of 0.000 <0.05 which means that there is a positive and significant influence.